Analisis Kesalahan Mahasiswa Pendidikan Matematika Dalam Menyelesaikan Soal Deret Tak Hingga Berdasarkan Teori Kastolan - Sitorus, Grace Elicia; Sibarani, Khoirunnisa; Samosir, Martha Indah; Manurung, Hendra Cahyadi; Simanullang, Michael Christian (Mandalika Mathematics and Educations Journal, 2025)
This study analyzes errors made by mathematics education students in solving problems related to infinite series, focusing on a topic known for its conceptual and procedural complexity. Based on Kastolan's Theory, this research builds upon previous findings regarding students’ difficulties with infinite series material. A qualitative descriptive approach was employed to analyze the responses of 10 mathematics education students at Universitas Negeri Medan, who had taken or were currently taking the real analysis course, particularly the topic of infinite series. The participants were randomly selected. Data were collected through a structured Google Form questionnaire and two open-ended questions assessing convergence and the summation of geometric series. The errors were categorized into three types: conceptual errors, such as misinterpretation of convergence criteria (10%); procedural errors, including incorrect determination of the ratio (30%); and technical errors, such as calculation mistakes (40%), with percentages calculated using the formula . The findings indicate that while conceptual understanding was relatively sound, technical errors were most prevalent, especially in fraction operations and symbolic manipulation. The study recommends instructional approaches that integrate concept reinforcement, procedural scaffolding, and computational accuracy training. This research contributes to mathematics education by providing empirical evidence on common error patterns in advanced calculus and by encouraging instructors to strengthen teaching strategies that systematically combine conceptual understanding and procedural skills in solving infinite series problems.